The Influence of Environmental, Social, and Governance (ESG) Performance on Company Performance - Marlina Kurniawan (PT Mattawang Mediatama Solution, 2023)
This study analyzes the effect of ESG performance on company performance in Malaysia public companies. The data sourced the Refinitiv Eikon in the 2021 period. The estimation of the data regression model can be determined in this study using Ordinary Least Square (OLS). The results of this study indicate that the higher the ESG score in a company, the company's performance will increase. Thus, ESG performance is considered to contribute to improving company performance. The analysis results can be used by management to make investment decisions on ESG whether it is worth the results, and for investors to be a consideration in determining their investment decisions.